Evolution and Comprehensive Analysis of DNaseI Hypersensitive Sites in Regulatory Regions of Primate Brain-Related Genes - Lu, Yueer; Wang, Xiao; Yu, Hang; Li, Jianlin; Jiang, Zhiqiang; Chen, Bangwei; Lu, Yueqi; Wang, Wei; Han, Chongyin; Ouyang, Ying; Huang, Lizhen; Chen, Chunbo; et al. (Frontiers in Genetics, 2019)
How human brain differs from non-human primates is largely unknown and the complex drivers on genomic scope remain unclear. In this study, we selected 243 brain-related genes in Gene Ontology and leveraged 184,113 DNaseI hypersensitive sites (DHSs) within their regulatory regions. As a result, 2397 DHSs (6%) were accelerated evolved (aceDHSs), of which was much higher compared to genome-wide scale. Regulated targets of brain-aceDHSs were enriched in brain development and exhibited differential expression between human and chimpanzee. Through alignment, 61 potential human-specific transcription factor binding sites located in brain-aceDHSs, including CTCF, FOXH1 and FOXQ1. Furthermore, based on GWAS, Hi-C and eQTL data, 16 GWAS SNPs and 82 eQTL SNPs were located in brain-aceDHSs and regulated genes that related with brain development or diseases. Among brain-aceDHSs, using both CRISPR-Cas9 and western blotting, we confirmed that one aceDHS enhanced the expression of GPR133, a gene that influenced glioblastoma, indicating variants within DHSs could be potential SNPs of brain disorders. These findings suggested that brain-related gene regulatory regions are under adaptive evolution and contribute to the differential expression profiles among primates, providing new insights into the genetic basis of brain phenotypes or disorders between humans and other primates.